Sustainable tourism as an effort to preserve culture and environment in Udjo Ecoland, Cimenyan, Bandung Regency - Azmi Kautsar Alim; Mohammad Sapari Dwi Hadian; Evi Novianti; Any Ariani Noor (Jurnal Pariwisata Pesona, 2023)
Mass tourism is an industrial sector that drives economic development significantly but causes many environmental and socio-cultural problems. This is clearly illustrated in Cimenyan, where land conversion for tourism development causes environmental damage and social problems. This research aims to analyze the entity of Udjo Ecoland as a tourism product and its elaboration in the framework of sustainable tourism as an effort to preserve the environment and culture. Qualitative descriptive analysis method was used to get a comprehensive and in-depth picture. Data were obtained from primary sources in the form of field observations and interviews and secondary data in the form of literature review. The results showed that Udjo Ecoland had all four components of tourism destinations (4A) and fulfilled the three pillars of sustainable tourism. The presence of Udjo Ecoland then gradually leads to efforts to preserve culture and environment by forming a new culture that elaborates noble values into a sustainable tourism framework and builds community awareness to create independence with an environmental perspective. Through sustainable tourism management, Udjo Ecoland has succeeded in making a positive contribution to environmental damage and social problems in Cimenyan as an effort to preserve culture andÂ environment.